The The analysis of Jean Baptiste Grenouille's desire in Patrick Suskind's perfume: The Story of Murderer - yusuf bakhtiar (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Analyzing Jean Baptiste Grenouille through a Lacanian lens offers a compelling exploration of desire, identity, and the unconscious in "Perfume: The Story of a Murderer." Jean Baptiste's character exemplifies Lacan's concept of desire as a fundamental aspect of human subjectivity, shaped by unconscious drives and symbolic representations. The aspect of Lacanian theory relevant to Jean Baptiste is the idea of the "mirror stage," where an individual forms their sense of identity through identification with external images. Jean Baptiste's obsession with capturing and possessing the perfect scent can be seen as a quest for self-recognition and identity formation. His desire to create the ultimate perfume reflects a longing for a perfected self, mirroring Lacan's notion of the ego ideal. Moreover, Lacan's concept of the "objet petit a," the elusive object-cause of desire, helps elucidate Jean Baptiste's relentless pursuit of scent. The perfume, particularly that of young virginal girls, serves as the object of his desire, representing an unattainable ideal that he seeks to possess. This desire is not merely driven by physical attraction but also by a deeper longing for wholeness and completion, as suggested by Lacan. The researcher try to find The reflection of Desire in the novel and show what the effect of desire it self using Jacques Lacan theory of desire The analysis shows that Desire is not only about what the subject wants, but many aspects influence the formation of a desire using Lacan's theoretical method. The representation of desire in Grenouille extends beyond conscious control, deeply rooted in his psychological condition